Analysis of multiscale methods for time‐harmonic Maxwell's equations. Issue 1 (25th October 2016) - Henning, Patrick; Ohlberger, Mario; Verfürth, Barbara
Abstract: We shortly revisit the Heterogeneous Multiscale Method (HMM) for the time‐harmonic Maxwell's equations in locally periodic media as introduced in [1]. The optimal a priori bounds in theH (curl) and H −1 norm predicted theoretically are justified by a numerical example in this contribution. The setting consists of a periodic inverse permeability, inspired by [2], and as reference solution a computation on a fine (well‐resolved) grid is used. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)